Demand for Library and Information Science professionals in Spain: Analysis of the names of job offers and tasks and skills involved - Martínez Comeche, Juan Antonio; Carpallo Bautista, Antonio; Burgos Bordonau, Esther; de Francisco OImos, José María (Revista General de Información y Documentación, 2015)
The aim of this study is to examine the causes of the decline in demand for specialized training in Library and Information Science despite the increasingly role of information and documentation in the labor market. A sample of public and private job offers announced during 2012 and 2013 at the state level were collected, analyzing the academic training, tasks and skills associated with the most frequent denominations. It is concluded that academic training in Library and Information Science is required when the job is linked to the treatment and management of documents, while our degrees are not considered appropriate when the work is related to information management and technology, these last jobs being more important for our graduates now and in the future.